2nd IET International Conference on Intelligent Signal Processing 2015 (ISP) 2015
DOI: 10.1049/cp.2015.1784
|View full text |Cite
|
Sign up to set email alerts
|

Human authentication with finger textures based on image feature enhancement

Abstract: The main goal of this paper is to authenticate people according to their finger textures. We propose to extract Finger Texture (FT) features of the four finger images (index, middle, ring and little) from a low resolution contactless hand image. Furthermore, we apply a new Image Feature Enhancement (IFE) method to enhance the FTs. The resulting feature image is segmented and a Probabilistic Neural Network (PNN) is employed as an intelligent classifier for recognition. Experimental results illustrate that the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(41 citation statements)
references
References 17 publications
0
41
0
Order By: Relevance
“…This rule is usually employed in the FLF and it has been cited that this method has the ability to achieve a significant performance [49]. Interestingly, this method has achieved acceptable EER in the SLF as the input data to the biometric system were doubled and increasing the input information will enhance the biometric system performance as confirmed in [29]. Nonetheless, this rule cannot be considered as a best choice between all the fusion levels, where it has benchmarked inferior EER value in the ScLF.…”
Section: Fusion Level Eer Average Summation Multiplication Maximum MImentioning
confidence: 82%
See 4 more Smart Citations
“…This rule is usually employed in the FLF and it has been cited that this method has the ability to achieve a significant performance [49]. Interestingly, this method has achieved acceptable EER in the SLF as the input data to the biometric system were doubled and increasing the input information will enhance the biometric system performance as confirmed in [29]. Nonetheless, this rule cannot be considered as a best choice between all the fusion levels, where it has benchmarked inferior EER value in the ScLF.…”
Section: Fusion Level Eer Average Summation Multiplication Maximum MImentioning
confidence: 82%
“…Then, the score fusion was executed after the matching operations. In 2015, Al-Nima et al [29] suggested extracting all the FT parts of the four fingers. In this work, it was cited that collecting more FT patterns will lead to increase the recognition performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations